Towards coordinated multi-agent exploration problem via segmentation and reinforcement learning - Chen, Zichen (Nanyang Technological University, 2020)
Exploring an unknown environment by multiple autonomous robots is a major challenge in the robotics domain. The robot or agent needs to incrementally construct a model or a map representation of the environment while performing its domain tasks like surveillance, search and rescue tasks, and cleaning. What the robot should do or where it should go to visit next can only be determined after the map is constructed at least partially.